Konstruksi Pendidikan Seksualitas dalam Perspektif Islam Pada Buku Ajar Pendidikan Al Islam Kelas IV SD Muhammadiyah - Amalia Purtri Rurina; Difa'ul Husna (Yayasan Azhar Amanaa Yogyakarta, 2026)
Sex education for elementary school children is important to build self-awareness, moral responsibility, and the ability to maintain personal dignity according to religious values. The Al-Islam Education textbook plays a strategic role in shaping this understanding through the material presented to students. However, research on how Islamic sex education is constructed in Al-Islam Education textbooks at the elementary school level is still limited. This study aims to analyse the construction of Islamic sex education as well as the relevance of sexual education construction in the Al-Islam Education textbook for 4th-grade students at Muhammadiyah Elementary School. This study uses a qualitative approach with content analysis methods on the Islamic education book for 4th grade at SD Muhammadiyah. The research data consists of learning materials related to puberty, self-changes, obligations after puberty, awrah, and social ethics, which are analysed from an Islamic education perspective. The results show that sexuality education in the book is constructed through four main aspects: awareness of body changes, religious responsibility, self-honour protection, and social ethics. However, further development of the textbook is still needed, particularly in strengthening aspects of child self-protection and presenting more practical materials suitable for elementary school students.